Meteorological observations at Syowa Station in 2007 by the 48th Japanese Antarctic Research Expedition - Tatsuo Nakamura; Yukihiro Nomura; Tetsuya Shimamura; Syouhei Iwatsubo; Kazumasa Matsuzawa (National Institute of Polar Research, 2012)
This report describes the results of meteorological observations at Syowa Station from February 1st, 2007 to January 31st, 2008, carried out by the Meteorological Observation Team of the 48th Japanese Antarctic Research Expedition(JARE-48). The observation methods, instruments and statistical methods used by JARE-48 were almost the same as those used by the JARE-47 observation team. Remarkable weather phenomena observed during the period of JARE-48 are as follows.1) In October 2007, there were 6 blizzards and 15 blizzard days, and the monthly mean temperature was -10.8℃, which was the highest record for Syowa Station.2) In November 2007, the monthly sunshine duration at Syowa Station was 474.8 hours, which was the longest record, and minimum humidity 21% updated minimum.3) The monthly mean amount of total ozone over Syowa Station in July was 233 m atm-cm, which was the lowest record. The amount of total ozone became lower than or equal to 220 m atm-cm from mid-August to end of October. On October 5th, the amount of total ozone was 138 m atm-cm, which was the lowest value in 2007.